Development ofKapok Based Plumbum and Cadmium Detection From Taste Sensor Technology - Ibrahim, Mohd Isyhar Fikri (Universiti Teknologi PETRONAS, 2009)
To many people, heavy metal pollution is a problem associated with areas of intensive industry. However, roadways and automobiles now are considered to be one of the largest sources of heavy metals. Zinc, copper, cadmium and lead are three of the most commonheavy metals releasedfrom road travel. Lead concentrations, however, consistently have been decreasing since leaded gasoline was discontinued. In modern societies, environmental pollution by bacteria, organic chemicals and heavy metal ions is becoming more and more severe. Lead is a toxic heavy metal element, associated with various adverse health effects. Lead ions (Pb2+) easily accumulate in the environment and produces toxic effects in plants and animals, even at low concentrations, since Pb2+ is not biodegradable. It is therefore crucial and of great importance to develop a method for the rapid and sensitive determination of lead as well as for cadmium. Based onthe taste sensor technology, the occurrence of heavy metals can be detected and quantified. These are made possible through application of some potential heavy metal detection material such as Kapok, castor seed hull and others as taste sensor electrodes that will 'taste' if heavy metal occurs. The types of heavy metal detected will be largely depends on what type of material used. In this research project, Kapok were incorporated as a sensing material into a modified carbon paste electrode to detect lead as a model heavy metal pollutant. Furthermore, we found that Kapok presents some good response in terms of detecting lead after tested in anodic stripping voltammetry analysis. This means that Kapok have great potential as a heavy metal detection material if it is further developed. Hence, after detecting these heavy metals, we will then prevent people from using solutions for example water; when it wasdetected to contain above safe level ofheavy metals in it.